Are agricultural sustainability and resilience complementary notions? Evidence from the North European agriculture. (January 2022) - Volkov, Artiom; Morkunas, Mangirdas; Balezentis, Tomas; Streimikiene, Dalia
Abstract: This study aims to investigate the relationship between sustainability and resilience concepts in agriculture. First, we discuss the theoretical preliminaries related to the definition of these two concepts. Indeed, the literature considers sustainability as a proxy for resilience and vice versa in the context of agriculture. Intuitively, one may expect that sustainability and resilience are positively correlated. Second, we challenge these insights by embarking on empirical analysis directed at the Northern European countries (Denmark, Estonia, Finland, Latvia, Lithuania and Sweden) that are member states of the European Union. The criteria describing sustainability and economic resilience are identified for the empirical analysis. Third, the criteria decision making is applied to derive the composite indicators. The contemporaneous correlation between the composite indicators of sustainability and economic resilience is rather weak across the analyzed countries. However, the correlation increases in case the first-order differences of the composite indicators are considered. Therefore, economic resilience indicators cannot be replaced by sustainability-related ones and economic resilience should be taken as an additional facet of the economic sustainability when developing composite indicators. Highlights: The indicators identifying agricultural sustainability and resilience are established. The multi-criteria approach is taken for aggregation. The case of the Northern Europe is considered. The direct relationship between agricultural sustainability and economic resilience is observed. The complementarity of the two notions is observed.